2009
DOI: 10.1007/s12020-009-9268-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 1 beta (IL-1β) promoter C [−511] T polymorphism but not C [+3953] T polymorphism is associated with polycystic ovary syndrome

Abstract: PCOS is a complex multifactorial disorder involving a number of genetic and environmental factors. One of the genetic factors that has been associated with PCOS is Interleukin 1 beta (IL-1β), is an important inflammatory cytokine that plays a regulatory role in both the body's immune and the inflammatory responses. All these responses appear to be are also affected in at least some women with PCOS. To investigate the possible association of polymorphisms of the IL-1β gene with the occurrence and clinical chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
1
19
1
Order By: Relevance
“…Eight publications were excluded for insufficient or uncorrelated data according to our inclusion criteria [9,11,10,14,13,23,24,30]. Finally, 18 articles met the inclusion criteria and were selected [8,7,27,12,28,18,15,17,20,19,22,21,25,26,29,31,16]. The study selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight publications were excluded for insufficient or uncorrelated data according to our inclusion criteria [9,11,10,14,13,23,24,30]. Finally, 18 articles met the inclusion criteria and were selected [8,7,27,12,28,18,15,17,20,19,22,21,25,26,29,31,16]. The study selection process is shown in Fig.…”
Section: Search Resultsmentioning
confidence: 99%
“…For IL-1A -889C>T (rs1800587), 310 cases and 279 controls from 2 studies [25,20] were analyzed. For IL-1B -511C>T (rs16944), we looked at 482 cases and 421 controls from 4 studies [25,8,18,16]. For the IL-1B +3953C>T polymorphism (rs1143634) in exon 5, 223 cases and 188 controls from 2 studies were included [18,25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Indeed, recent studies have identified several genes that might be relevant in PCOS pathogenesis [14], such as anti-Müllerian hormone [82,83]; gonadotropin-releasing hormone [71], aromatase [84], androgen receptors [85], 17β-hydroxysteroid dehydrogenase type 5 and type 6 [86], interleukins [87,88], vascular endothelial growth factor [89] or genes involved in folliculogenesis [90].…”
Section: Other Genesmentioning
confidence: 99%
“…Italian [171] Turkish [172,173] HLA-A (6p21.3, major histocompatibility complex class I, A) A11 Japanese [174] HLA-B (6p21.3, major histocompatibility complex class I, B) B39 Japanese [174] HLA-C (6p21.3, major histocompatibility complex class I, C) All alleles Japanese [174] HLA-DRB1 (6p21.3, major histocompatibility complex class I, DR beta 1) *0403 Japanese [174] HFE (6p21.3, haemochromatosis protein) rs1799945, rs1800562 Spanish [175] HMGCR (5q13.3-q14, HMG-CoA reductase) rs4629571 North American [176] IL1A (2q14, interleukin 1 ) rs1800587 Austrian [177] Chinese [178] rs16944 Chinese [179,180] Austrian [177] IL1B (2q14, interleukin 1 ) rs1143634…”
Section: C825tmentioning
confidence: 99%
“…Chinese [179] Austrian [177] Chinese [180] IL1R ( 2q12, interleukin 1 receptor) VNTR Chinese [111] rs1800797 Spanish [181] rs1800796 Spanish [181] …”
Section: C825tmentioning
confidence: 99%